2018
DOI: 10.3892/etm.2018.6970
|View full text |Cite
|
Sign up to set email alerts
|

Glucose affects cell viability, migration, angiogenesis and cellular adhesion of human retinal capillary endothelial cells via SPARC

Abstract: The expression of secreted protein acidic and rich in cysteine (SPARC) has been recently identified to be associated with the pathology of diabetic retinopathy. Therefore, the present study aimed to evaluate the regulatory role of SPARC in human retinal capillary endothelial cells (HRCECs), following exposure to a high glucose environment in vitro. The cell viability, migration, angiogenesis, permeability and SPARC expression levels of HRCECs were measured following treatment with different concentrations of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
3
1
1
Order By: Relevance
“…Regarding vascular proliferation, there was greater proliferation in G3 than in G1 and G2 on both the 14th and 28th postoperative days. This finding contrasts with some studies that suggest that hyperglycaemia increases angiogenesis and that glucose increases angiogenesis and accelerates healing in normal and diabetic rats 24 27 .…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding vascular proliferation, there was greater proliferation in G3 than in G1 and G2 on both the 14th and 28th postoperative days. This finding contrasts with some studies that suggest that hyperglycaemia increases angiogenesis and that glucose increases angiogenesis and accelerates healing in normal and diabetic rats 24 27 .…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with the literature, this research found that participants who reported using HG-induced retinal pigment epithelium played an important role in the development of DR. In addition, previous studies showed that HG-induced HRCEC inhibition of cell viability, migration, angiogenesis, and cell adhesion was reversed by inhibition of SPARC expression (44). In our studies, we found that HG-induced apoptosis can be reversed by ablation of SPARC.…”
Section: Discussionsupporting
confidence: 74%
“…However, genes like COL4A1 ( Alavi et al, 2016 ), COL4A2 ( Alavi et al, 2016 ), and FN1 ( Moradipoor et al, 2016 ) are found to have association with the DR pathogenesis. Studies have also found SPARC ( Fu et al, 2019 ), IL-6 ( Rojas et al, 2011 ), and MMP9 ( Kowluru et al, 2012 ) playing roles in DR development by affecting one or more factors responsible for DR like angiogenesis, inflammation, etc.…”
Section: Resultsmentioning
confidence: 99%